2015
DOI: 10.3109/08990220.2015.1091771
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of passive and active movement on vibrotactile detection thresholds of the Pacinian channel and forward masking

Abstract: We investigated the gating effect of passive and active movement on the vibrotactile detection thresholds of the Pacinian (P) psychophysical channel and forward masking. Previous work on gating mostly used electrocutaneous stimulation and did not allow focusing on tactile submodalities. Ten healthy adults participated in our study. Passive movement was achieved by swinging a platform, on which the participant's stimulated hand was attached, manually by a trained operator. The root-mean-square value of the move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 59 publications
1
5
2
Order By: Relevance
“…However, the waveform frequency of each pulse was around 150 Hz, which typically activates the Pacinian receptor class. Nevertheless, estimated detection thresholds in the current study (approximately 70 µm) are considerably higher compared to the thresholds reported for the Pacinian receptor system, which are typically around 1 µm or less (Gescheider et al, 2009;Yildiz and Güçlü, 2013;Yıldız et al, 2015).…”
Section: Discussion (Experiments 1)contrasting
confidence: 80%
See 1 more Smart Citation
“…However, the waveform frequency of each pulse was around 150 Hz, which typically activates the Pacinian receptor class. Nevertheless, estimated detection thresholds in the current study (approximately 70 µm) are considerably higher compared to the thresholds reported for the Pacinian receptor system, which are typically around 1 µm or less (Gescheider et al, 2009;Yildiz and Güçlü, 2013;Yıldız et al, 2015).…”
Section: Discussion (Experiments 1)contrasting
confidence: 80%
“…In the current experiment, we did not find any significant effect of the scanning speed on the detection thresholds; the exploratory speed of the hand during active exploration was on average 87 mm/s. It appears that the detrimental effect of movements on the detection threshold is dependent on the speed of the sensing hand (Cybulska-Klosowicz et al, 2011;Yıldız et al, 2015) and that the speed observed in the current study was much lower than the critical speed (approximately 200 mm/s) at which tactile sensitivity decreases. Moreover, fine texture perception requires movement and sensory gating would impede the whole process of perception.…”
Section: Discussion (Experiments 1)contrasting
confidence: 50%
“…Although both passive and active movements elevated detection thresholds at higher speeds, the effect of forward masking was constant as the movement condition varied. The finger speeds used in the electrovibration study reported here were lower than the fast speed range used in the gating study [54]. Therefore, there was probably not much gating effect in our study, and the masking functions were similar to those reported previously.…”
Section: Previous Vibrotactile Masking Studiessupporting
confidence: 82%
“…If the normal force and or scan speed of a participant were not in the desired range (0.1-0.6 N, and ± 25% of 50 mm/s), the trial was repeated until a measurement within the range was obtained. We selected this range based on the normal forces and speeds reported in the literature as relevant to tactile exploration [53], [54]. Figs.…”
Section: Threshold Experimentsmentioning
confidence: 99%
See 1 more Smart Citation